2013
DOI: 10.1002/ange.201307460
|View full text |Cite
|
Sign up to set email alerts
|

Trienamines Derived from Interrupted Cyclic 2,5‐Dienones: Remote δ,ε‐CC Bond Activation for Asymmetric Inverse‐Electron‐Demand Aza‐Diels–Alder Reaction

Abstract: A special challenge in the field of asymmetric catalysis is the realization of remote stereocontrol.[1] The problem can be extended to remote sites which must be activated to ensure better reactivity. While most early examples of remote asymmetric inductions rely on enzyme catalysis or intramolecular relay of chiral information through the substrate, [2] current studies have demonstrated that chiral catalysts can facilitate enantioselectivity in variety of reactions.[3] In particular, our group and the group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…All chemicals including α-angelica lactone 2a were used without purification as commercially available unless otherwise noted, and the other butenolides were prepared according to the literatures [15]. α,β-Unsaturated imines 2 and 7 were prepared according to the literature procedures [16]. The tertiary amines 1b and 1c were also synthesized according to the literature procedures [21,22], and others were commercial available.…”
Section: General Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All chemicals including α-angelica lactone 2a were used without purification as commercially available unless otherwise noted, and the other butenolides were prepared according to the literatures [15]. α,β-Unsaturated imines 2 and 7 were prepared according to the literature procedures [16]. The tertiary amines 1b and 1c were also synthesized according to the literature procedures [21,22], and others were commercial available.…”
Section: General Methodsmentioning
confidence: 99%
“…On the other hand, our group recently developed a series of asymmetric reactions involving cyclic 1-azadienes containing a 1,2-benzoisothiazole-1,1-dioxide motif [16][17][18][19]. They are stable materials, and readily available from diverse saccharins and aldehydes.…”
Section: Introductionmentioning
confidence: 99%
“…[4] In addition, the application of interrupted b-allylic cyclic enones could accomplish either d,e-regioselectivei nverse-electron-demand cycloadditions or e-regioselective bisvinylogous additions (Scheme 1b). [5] In contrast, cross-conjugated tri enaminei ntermediates would be preferably generatedw ith cyclic 2,4-dienonem aterialsi nt he presenceo faprimary amine catalyst, and a',b-regioselective formal [4+ +2] cycloadditions would occurw ith electron-deficient dienophiles (Scheme1c). [6] As ar esult, the application of structurally diverse polyunsatura-ted ketones ubstrates mayh ave high potential to uncover new reactionmodes by amine-based catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, only the Michael adduct 3a' ' was obtained in al ow yield by using the conjugated enone 2a' ' (entry 3), indicating that the inducing effect of the previously positioned b,g-C=Cb ond would be crucial for generating the required dienolate intermediate (Scheme 1d). [7] Encouraged by these results, we explored the potential asymmetric version by the cooperative catalysis of Pd(OAc) 2 and chiral PTC. [8] While poor yield and enantioselectivity were obtained with ammonium salt C1 (Table 1, entry 4), it was found that better reaction could be attained by employing the l-amino-acid-derived phosphonium salts C2-C4 (entries 5-7), [9] and agood ee value was gained with C4 at À10 8 8C(entry 8).…”
mentioning
confidence: 99%
“…Fort he reactions with 2a,u niformly high to excellent enantioselectivities were obtained by introducing diverse substituents into the oxindole core of the nucleophiles 1 (entries 2-6), whereas slightly lower yields were observed for those with electron-withdrawing groups (entries 4-6). Outstanding enantiocontrol was attained for other 3-aryl-substituted oxindoles (entries [7][8][9]. Notably,a n oxindole bearing a1 -pyrrolyl group could be successfully applied (entry 10), and outstanding ee values were generally afforded by introducing various benzyl (entries [11][12][13] or [b] ee [%] [c] 1 [d] -K OAc Toluene 8--2 [d] TBAB KOAc Toluene 87 9-3 [d,e] TBAB KOAc Toluene 81 [b] ee [%] [c] 1H [e] The absolutec onfiguration of chiral 3n was determined by X-ray analysis of its derivative 12' ' (see the SupportingInformation).…”
mentioning
confidence: 99%